Pengelolaan Limbah Cair Perusahaan Tempe Kedelai di Desa Pliken Kecamatan Kembaran Kabupaten Banyumas Berdasarkan Perda Kabupaten Banyumas Nomor 8 Tahun 2018 Tentang Pengelolaan Air Limbah - Nurutami, Oktiana; Soediro, Soediro (UMPurwokerto Law Review, 2024)
Abstract One of them is the soybean processing industry in Banyumas Regency, especially in Pliken Village, Kembaran District, namely tempe processing. Tempe liquid waste contains high organic matter and high levels of Biological Oxygen Demand (BOD), Chemical Oxygen Demand (COD), which if directly discharged into water bodies, will clearly reduce the carrying capacity of the environment. Moreover, the factory does not have a liquid waste disposal permit, so it can be subject to administrative sanctions or laws and regulations regulated in Article 39 paragraphs (2) and (3) of Banyumas Regency Regional Regulation Number 8 of 2018.Â This research approach method uses normative juridical research. The data collection method is carried out to obtain data in a study using the library research method. The data obtained is analyzed using a qualitative method. Based on the results of research and discussion related to liquid waste management has not gone well, this is because entrepreneurs do not have a liquid waste disposal permit. Factors that become obstacles to the management of liquid waste in the tempeh industry, namely a). ignorance factor of the entrepreneurs themselves; b). education level factor; c). economic factors of entrepreneurs; d). government participation and law enforcement factors; e). community participation factors. Â Keywords: Management, Liquid Waste, Tempe Industry Â Abstrak Salah satunya adalah industri pengolahan kedelai yang ada di Kabupaten Banyumas khususnya di Desa Pliken Kecamatan Kembaran yaitu pengolahan tempe. Limbah cair tempe mengandung bahan organik tinggi dan kadar Biological Oxygen Demand (BOD), Chemical Oxygen Demand (COD) yang cukup tinggi pula, jika langsung dibuang ke badan air, jelas sekali akan menurunkan daya dukung lingkungan. Terlebih lagi pabrik tersebut tidak mengantongi izin pembuangan limbah cair, maka dapat dikenakan sanksi administratif atau peraturan perundang-undangan yang diatur dalam Pasal 39 ayat (2) dan (3) Peraturan Daerah Kabupaten Banyumas Nomor 8 Tahun 2018.Â Metode pendekatan penelitian ini menggunakan penelitian yuridis normatif. Metode pengumpulan data dilakukan untuk memperoleh data dalam suatu penelitian dengan metode kepustakaan (library research). Data yang diperoleh dianalisa dengan metode kualitatif. Berdasarkan hasil penelitian dan pembahasan terkait pengelolaan limbah cair belum berjalan dengan baik, hal ini para pengusaha tidak memiliki izin pembuangan limbah cair. Faktor-faktor yang menjadi kendala pengelolaan limbah cair industri tempe yaitu a). faktor ketidaktahuan dari pengusaha itu sendiri; b). faktor tingkat pendidikan; c). faktor ekonomi pengusaha; d). faktor partisipasi pemerintah dan penegakan hukum; e). faktor peran serta masyarakat. . Kata kunci: Pengelolaan, Limbah Cair, Industri Tempe